Pengaruh Experiential Marketing Terhadap Minat Beli Ulang Milo Cheese di Kopiria Tanah Grogot - Karlina Karlina; Achmad Aprianor Firdaus; Roy Sunarto (Universitas Katolik Widya Karya Malang, 2023)
The purpose of this study was to determine the effect of experiential marketing (X) on interest in repurchasing (Y) milo cheese at Kopiria Tanah Grogot. The sample in this study were consumers or buyers of Milo cheese at Kopiria in Tanah Grogot. The sampling technique in this study was purposive sampling and the number of samples in this study were 60 people. Consumers or buyers as a sample of this study were given a questionnaire consisting of 21 questions. Responses to the questionnaire were tested for validity and reliability prior to multiple linear regression analysis using the statistical product and service solution (SPSS) application.The results of the validity test stated that all statements consisting of 21 items were valid because rcount>rtable (0.2542). The results of the reliability test for all questions stated that reliability was acceptable because the Cronbach'alpha value> 0.6 or 0.791> 0.6.The results of multiple linear regression analysis obtained the regression equation, namely Y = 0.758 +- 0.035 X1+0.430X2 +- 0.007X3 + 0.461X4 + -0.015X5. Coefficient value correlation (R) of 0.783 means that between experiential marketing (X) has a strong relationship to repurchase intention (Y). The coefficient of determination (Adjusted R2) is 0.634, meaning that the variation in the experiential marketing variable (X) can contribute to repurchasing interest (Y) Milo cheese at Kopiria Tanah Grogot is 63.4% while the rest is explained by other factors not examined at (100- 63.4)% = 36.6%. The simultaneous results (F test) show that the value of Fcount>Ftable (17.150>2.38) so it can be concluded that there is an influence between the experiential marketing variable (X) on repurchase intention (Y). Then the results of the partial test (t test) show that the value of tcount > ttable on feel (X2) is 5.193> 2.004 and action (X4) is 4.567 > 2.004 which means there is an influence on repurchasing interest (Y) Milo cheese at Kopiria Tanah Grogot while the value tcount < ttable on sense (X1), think (X3) and relate (X5) which means there is no effect on repurchasing interest (Y) Milo cheese at Kopiria Tanah Grogot..